Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/oby.21793
|View full text |Cite
|
Sign up to set email alerts
|

HIV infection does not prevent the metabolic benefits of diet‐induced weight loss in women with obesity

Abstract: Objective To test the hypothesis that HIV infection impairs the beneficial effects of weight-loss on insulin-sensitivity and adipose-tissue inflammation and endoplasmic reticulum (ER) stress. Methods A prospective clinical trial to evaluate the effects of moderate diet-induced weight-loss on body-composition, metabolic function and adipose-tissue biology in women with obesity who were HIV-seronegative (HIV−) or HIV-positive (HIV+). Body-composition, multi-organ insulin-sensitivity (assessed by using a 2-stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…A complete review of therapeutic options for obesity and visceral adiposity in treated HIV infection is beyond the scope of this article, although a consensus guideline has recent been published[102]. To date, data on the efficacy of weight loss and dietary interventions in HIV are mixed, although structured exercise with or without dietary intervention reduces abdominal obesity in most studies[103107], and disproportionate SAT loss has not been observed, eliminating fear of worsening of lipoatrophy in persons with mixed lipodystrophy. Based on available data, ≥30 minutes of moderate-intensity physical activity most days of the week plus reduction of caloric intake at least 500 kcal/day below usual intake is generally recommended to attain and sustain significant (≥5%) weight loss[108, 102].…”
Section: Interventionsmentioning
confidence: 99%
“…A complete review of therapeutic options for obesity and visceral adiposity in treated HIV infection is beyond the scope of this article, although a consensus guideline has recent been published[102]. To date, data on the efficacy of weight loss and dietary interventions in HIV are mixed, although structured exercise with or without dietary intervention reduces abdominal obesity in most studies[103107], and disproportionate SAT loss has not been observed, eliminating fear of worsening of lipoatrophy in persons with mixed lipodystrophy. Based on available data, ≥30 minutes of moderate-intensity physical activity most days of the week plus reduction of caloric intake at least 500 kcal/day below usual intake is generally recommended to attain and sustain significant (≥5%) weight loss[108, 102].…”
Section: Interventionsmentioning
confidence: 99%
“…Intensive lifestyle modification may result in 8% weight reduction, although this is rarely achieved in clinical practice and the interventions required to achieve this may be difficult to sustain. Lifestyle interventions may also be slightly less effective in black populations [57], but seem to confer similar benefits to people with and without HIV [58,59].…”
Section: Management Of Obesitymentioning
confidence: 99%
“…However, Fitch et al reported that intensive lifestyle modification significantly improved important cardiovascular risk indices in PLWH with MetS and suggested that lifestyle modification might be a useful strategy to decrease cardiovascular risk in PLWH [ 75 ]. A prospective clinical trial evaluated the effect of moderate diet-induced weight loss in obese HIV-positive women and showed that moderate diet-induced weight loss improves multi-organ insulin sensitivity in HIV-positive women to the same extent as in HIV-negative women [ 76 ].…”
Section: Management Of Weight To Control Metsmentioning
confidence: 99%